Evaluación de diferentes métodos pregerminativos y tipos de sustratos en el crecimiento inicial de Gmelina arborea Roxb. a nivel de vivero - Bustamante Moyan, Dialis Isabel (2022)
The species G. arborea is one of the species with the highest value that exists in terms of its timber use, which is why plantations of this species are established in various parts of Ecuador in order to be able to take advantage of its wood in the future. The main objective of the research was to determine the different characteristics that the seedlings of this species